2007
DOI: 10.1002/eji.200636545
|View full text |Cite|
|
Sign up to set email alerts
|

MHC‐peptide‐specific antibodies reveal inefficient presentation of an HLA‐A*0201‐restricted, Melan‐A‐derived peptide after active intracellular processing

Abstract: MHC-peptide-specific Fab antibodies binding to HLA-A*0201 complexes presenting the wild-type EAAGIGILTV (EAA) or analogue Melan-A 10-mer ELAGIGILTV (ELA) peptide were generated to study efficacy of peptide processing and presentation. None of the selected Fab antibodies detected the naturally processed EAA/HLA-A*0201 complex on melanoma tumor cells, confirming the known low peptide number on the cell surface. To study the effect of peptide presentation and processing in more detail, genes coding for the A27L-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…In general Mart-1 expression levels on melanoma cell lines (such as Gmel) range from low to moderate levels (99). Also, Renner and colleagues showed that endogenous antigen processing of the decamer (Melan-A) protein or its A27L-mutated variant results in inefficient presentation of these peptides both wt and 27L mutant by HLA-A2-positive tumor cell lines (98). Therefore, since the Gmel melanoma cell line in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In general Mart-1 expression levels on melanoma cell lines (such as Gmel) range from low to moderate levels (99). Also, Renner and colleagues showed that endogenous antigen processing of the decamer (Melan-A) protein or its A27L-mutated variant results in inefficient presentation of these peptides both wt and 27L mutant by HLA-A2-positive tumor cell lines (98). Therefore, since the Gmel melanoma cell line in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For selection of antibodies specific for wtP-7 or pP-7, a phagemid library expressing a large non-immune, semi-synthetic human Fab repertoire, containing 1.45 3 10 10 different antibody fragments, was used. 14 Selection was done as described by Held et al 15 Two peptides were used for selection: for wtP-7 Biot-SGGGGSRGTGALLLRGSL-LASGRAPRRA; for pP-7 Biot-SGGGGSRGTGALLLRG(pS)LLAS-GRAPRRA. Specifically bound phages were eluted and used to infect E. coli strain TG1 (30 min at 37 C), and bacteria were grown overnight at 30 C on agar.…”
Section: Expression Of Pp2a Subunits B In Lclsmentioning
confidence: 99%
“…30 For detection of SSX2 103-111 /HLA-A*0201 complexes after endogenous processing a ubiquitin/protein/reference (UPR)-based pEGFP vector was used. 31 The vectors encoded for EGFP/ Ubiquitin/Melan-A [26][27][28][29][30][31][32][33][34][35] or EGFP/ubiquitin/SSX2 103-111 fusion protein. In eukaryotic cells, the resulting fusion protein is cleaved co-translationally at the junction between EGFP-ubiquitin and the peptide of interest by ubiquitin-specific proteases.…”
Section: Flowcytometrymentioning
confidence: 99%
“…We used several antigen presenting cells to demonstrate that the Fab-VIE1 could bind to the specific MHC-peptide complex not only in its recombinant soluble form, but also in the native form expressed on the cell surface. Soluble Fab-VIE1 reacted with SSX2 103-111 peptide loaded T2 cells and HLA-A*0201 1 EBV-transformed lymphoblastoid cell line, but not with cells loaded with one of 6 different HLA-A*0201-binding peptides, SSX2 [41][42][43][44][45][46][47][48][49] , NY-ESO-1 157-165 , influenza matrix protein 58-66 , gp100 209-217 , Melan-A [26][27][28][29][30][31][32][33][34][35] and Carboanhydrase-IV 254-262 , respectively. No binding of Fab-VIE1 to the HLA-A*0201 2 EBV-transformed B-lymphocytes was observed, neither when pulsed with the SSX2 103-111 peptide nor with control peptides (Fig.…”
Section: Characterization Of Fab-vie1 With Specificity For Ssx2 103-1mentioning
confidence: 99%
See 1 more Smart Citation